Patient Surgical Outcomes When Surgery Residents Are the Primary Surgeon by Intensity of Surgical Attending Supervision in Veterans Affairs Medical Centers - T. Michael Kashner, PhD, JD, MPH; Paul B. Greenberg, MD, MPH; Andrea D. Birnbaum, MD, PhD; John M. Byrne, DO; Karen M. Sanders, MD; Mark A. Wilson, MD, PhD; Marjorie A. Bowman, MD, MPA (Annals of Surgery Open, 2023)
Objective:. Using health records from the Department of Veterans Affairs (VA), the largest healthcare training platform in the United States, we estimated independent associations between the intensity of attending supervision of surgical residents and 30-day postoperation patient outcomes. Background:. Academic leaders do not agree on the level of autonomy from supervision to grant surgery residents to best prepare them to enter independent practice without risking patient outcomes. Methods:. Secondary data came from a national, systematic 1:8 sample of n = 862,425 teaching encounters where residents were listed as primary surgeon at 122 VA medical centers from July 1, 2004, through September 30, 2019. Independent associations between whether attendings had scrubbed or not scrubbed on patient 30-day all-cause mortality, complications, and 30-day readmission were estimated using generalized linear-mixed models. Estimates were tested for any residual confounding biases, robustness to different regression models, stability over time, and validated using moderator and secondary factors analyses. Results:. After accounting for potential confounding factors, residents supervised by scrubbed attendings in 733,997 nonemergency surgery encounters had fewer deaths within 30 days of the operation by 14.2% [0.3%, 29.9%], fewer case complications by 7.9% [2.0%, 14.0%], and fewer readmissions by 17.5% [11.2%, 24.2%] than had attendings not scrubbed. Over the 15 study years, scrubbed surgery attendings may have averted an estimated 13,700 deaths, 43,600 cases with complications, and 73,800 readmissions. Conclusions:. VA policies on attending surgeon supervision have protected patient safety while allowing residents in selected teaching encounters to have limited autonomy from supervision.